ENabling Reduction of Low‐grade Inflammation in SEniors Pilot Study: Concept, Rationale, and Design. Issue 9 (22nd July 2017) - Manini, Todd M.; Anton, Stephen D.; Beavers, Daniel P.; Cauley, Jane A.; Espeland, Mark A.; Fielding, Roger A.; Kritchevsky, Stephen B.; Leeuwenburgh, Christiaan; Lewis, Kristina H.; Liu, Christine; McDermott, Mary M.; Miller, Michael E.; et al.
Abstract : Objectives: To test two interventions to reduce interleukin (IL)‐6 levels, an indicator of low‐grade chronic inflammation and an independent risk factor for impaired mobility and slow walking speed in older adults. Design: The ENabling Reduction of low‐Grade Inflammation in SEniors (ENRGISE) Pilot Study was a multicenter, double‐blind, placebo‐controlled randomized pilot trial of two interventions to reduce IL‐6 levels. Setting: Five university‐based research centers. Participants: Target enrollment was 300 men and women aged 70 and older with an average plasma IL‐6 level between 2.5 and 30 pg/mL measured twice at least 1 week apart. Participants had low to moderate physical function, defined as self‐reported difficulty walking one‐quarter of a mile or climbing a flight of stairs and usual walk speed of less than 1 m/s on a 4‐m usual‐pace walk. Intervention: Participants were randomized to losartan, omega‐3 fish oil ( ω ‐3), combined losartan and ω ‐3, or placebo. Randomization was stratified depending on eligibility for each group. A titration schedule was implemented to reach a dose that was safe and effective for IL‐6 reduction. Maximal doses were 100 mg/d for losartan and 2.8 g/d for ω ‐3. Measurements: IL‐6, walking speed over 400 m, physical function (Short Physical Performance Battery), other inflammatory markers, safety, tolerability, frailty domains, and maximal leg strength were measured. Results: Results from the ENRGISE Pilot Study will provide recruitment yields, feasibility, medication tolerance and adherence, and preliminary data to help justify a sample size for a more definitive randomized trial. Conclusion: The ENRGISE Pilot Study will inform a larger subsequent trial that is expected to have important clinical and public health implications for the growing population of older adults with low‐grade chronic inflammation and mobility limitations.